Dinâmica da vegetação de uma floresta paludosa no município de Rio Claro - SP - Guidelli, Rodrigo Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Swamp forests, are laid down in the lowlands, with almost permanent presence of water on the soil surface and generally occupy portions fairly flat. In 2003 a phytosociological survey was conducted of the tree and shrub component of a swamp forest established on a steep slope in Rio Claro - SP, through the use of 45 permanent plots of 10 mx 10 m (0.45 ha) divided into three blocks: 1, 2 and 3. The present study aimed to review these plots and discuss the dynamics of vegetation in the swamp forest in question period of eight years. Altogether 1529 individuals were found alive, belonging to 29 families and 47 species. It can be observed that there was a decrease of one family (Flacourtiaceae) and two species (Xylosma tweediana, Inga marginata) in relation to 2003. In general there was a loss not only in number of individuals, but basal area and species diversity. The Block 1 was the only one to show a positive balance in terms of numbers of individuals (2.75%); in Block 2, there was little variation (1.72%) which is negative; whereas Block 3 had the largest decrease, 19.18%. The mortality rate (2.74% / year) for the community remained higher than the recruitment (1.81% / year). There was a decrease (3.19%) of total basal area of the sample relative to 2003, with the highest relative dominance by Calophyllum brasiliense. The decline in diversity of species could be evidenced by the Shannon index, which was 2.0 nats.individual-1 and evenness of 0.52. The most important species (IVI) were Euterpe edulis, Calophyllum brasiliense and Magnolia ovata, together accounting for 59% of IVI community. High mortality and low recruitment rates indicate disturbances in the community, some factors such as proximity to roads, the different soil types associated with a high rate of water saturation and the declivity are crucial to the balance within the community

Florestas paludosas, encontram-se estabelecidas em solos hidromórficos, com presença quase permanente de água na superfície do solo e geralmente ocupem porções bastante planas. Em 2003 foi conduzido um levantamento fitossociológico do componente arbustivo-arbóreo de uma floresta paludosa estabelecida sobre um declive acentuado no município de Rio Claro – SP, por meio do uso de 45 parcelas permanentes de 10 m x 10 m (0,45 ha) divididas em três Blocos: 1, 2 e 3. No presente trabalho pretendeu-se reavaliar tais parcelas e discutir a dinâmica da vegetação na floresta paludosa em questão no período de oito anos. Ao todo foram encontrados 1529 indivíduos vivos, pertencentes a 29 famílias e 47 espécies. Pode-se observar que houve o decréscimo de uma família (Flacourtiaceae) e duas espécies (Xylosma tweediana, Inga marginata) em relação a 2003. No geral houve uma perda não apenas em número de indivíduos, mas área basal e diversidade de espécies. O Bloco 1 foi o único que apresentou um balanço positivo em termos de números de indivíduos (2,75%); no Bloco 2 houve pouca variação (1,72%) sendo esta negativa; já o Bloco 3 apresentou o maior decréscimo, 19,18% . A taxa de mortalidade (2,74%/ano) para a comunidade permaneceu maior que a de recrutamento (1,81%/ano). Houve uma diminuição (3,19%) da área basal total da amostra em relação á 2003, sendo a maior dominância relativa apresentada por Calophyllum brasiliense. A queda na diversidade de espécies pôde ser evidenciada pelo índice de Shannon, que foi de 2,0 nats.indivíduo-1 e a equabilidade de Pielou de 0,52. As espécies mais importantes (IVI) foram: Euterpe edulis, Calophyllum brasiliense e Magnolia ovata, perfazendo juntas 59% do IVI da comunidade. Altas taxas de mortalidade e baixas taxas de recrutamento indicam distúrbios dentro da comunidade; alguns fatores... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Dinamica de vegetação; Ecologia vegetal; Mortalidade; Florestas - Composição; Ecossistemas; Biodiversidade; Essencias florestais; Solos hidromorficos; Fazenda São José (Rio Claro, SP)